KORELASI LAMA INISIASI MENYUSUI DINI (IMD) TERHADAP PENGELUARAN ASI DI PUSKESMAS KALIBAGOR KABUPATEN BANYUMAS - Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
WHO (World Healt Organization) recommends initiation of breastfeeding early in the first hour of birth, exclusive breastfeeding for six months, continued with complementary feeding until the age of two years. This program is done by putting a newborn baby on his mother's chest and letting this baby crawl to find the mother's nipple for feeding. The important process that occurs is the baby will begin to squeeze the mother's nipple, aims to stimulate the breast milk (ASI) immediately produce and get out. Early breastfeeding initiation becomes very important in relation to maintaining breastmilk productivity. The more frequent breastfed babies the more prolactin hormone receptors will be increased The purpose of this study was to determine the long-term relationship of early breastfeeding initiation of breastfeeding time. The type of research used in this research is explanatory research with case control approach. The affordable population in this study were all patients who gave birth at Kalibagor Puskesmas Banyumas District. In this study using Chi Square statistical analysis. Based on the results of research, the average length of the implementation of the IMD is. Most breastfeeding occurs before the first 6 hours of post partum. There was no association between the duration of IMD and breastfeeding (p = 0.176) Keywords: early breastfeeding initiation, breast milk expenditure